Factors Influencing Tourists’ Bicycle Mode Choice in Luang Prabang District, Lao PDR - นุสนธิ์ พิพัฒน์ (Princess of Naradhiwas University Journal, 2018)
This article aims to present the analysis of factors influencing choosing bicycle as mode of transport choice by tourists in the district of Luang Prabang, Lao PDR. The sample group of 400 tourists at several tourist attractions in Luang Prabang were interviewed. Certain basic variables were tested for developing the Binary Logistic Regression Model which was used in forecasting the probabilities of using bicycle as mode of transport choice in Luang Prabang. The result of the study found that the variable effecting the personal factors was y = 0.877 + 0.0001 (income) + 0.058 (age) + 1.1945 (education). On the other hand, the variable effected the daily tour was y = 7.814 + 0.693 (possession car) + 2.194 (possession motorcycle) + 0.675 (possession bicycle) + 1.627 (footpath tour). But, the physical variable was y = 6.965 + 1.491 (parking place) + 0.812 (facilities) + 1.331 (blcycle way). The summary of the study was the stimulus factor for the attractive tourism and using bicycle for the tourism, in order to the promotion of government planning for the tourist using more bicycle in tourism.